2011
DOI: 10.4314/ijbcs.v5i2.72073
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation des rhizobactéries potentiellement promotrices de la croissance végétative du maïs dans différents agrosystèmes du Sud-Bénin

Abstract: Tel ; (+229)97123468 RESUME L'objectif de cette étude est de caractériser les rhizobactéries potentiellement promotrices de la croissance végétative ou encore en anglais « plant growth promoting rhizobacteria» (PGPR) vivant dans la rhizosphère de douze (12) différentes zones agroécologiques du sud-Bénin. Un échantillon composite de sol et de racines des plants de maïs est prélevé au niveau de 4 différents champs de producteurs par zone agroécologique. Des analyses agrochimiques et microbiologiques sont faites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 7 publications
(2 reference statements)
1
16
2
2
Order By: Relevance
“…The study conducted by Aliye et al (2008) has shown that P. fluorescens (strains PF9 and PF20) are responsible to increase the biomass of potato plants (Solanum tuberosum). The biomass improvements obtained in present study are greater than those obtained by Adjanohoun et al (2011). Indeed, Adjanohoun et al (2011) have registered an increase of 59.57% of the aerial biomass, induced by rhizobacteria P. fluorescens.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The study conducted by Aliye et al (2008) has shown that P. fluorescens (strains PF9 and PF20) are responsible to increase the biomass of potato plants (Solanum tuberosum). The biomass improvements obtained in present study are greater than those obtained by Adjanohoun et al (2011). Indeed, Adjanohoun et al (2011) have registered an increase of 59.57% of the aerial biomass, induced by rhizobacteria P. fluorescens.…”
Section: Discussioncontrasting
confidence: 41%
“…The biomass improvements obtained in present study are greater than those obtained by Adjanohoun et al (2011). Indeed, Adjanohoun et al (2011) have registered an increase of 59.57% of the aerial biomass, induced by rhizobacteria P. fluorescens. This difference is due to beneficial effects of chitosan that are added to PGPR effects.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…It is in this context that this prospective study was realized in prelude of the promotion of microbial biofertilizers based on native rhizobacteria. The agroecological characteristics of sites samples collected were presented in Table 1 [26]. Indeed, our result reflects the large soils diversity in Benin as Adjanohoun et al [26] reported other types of soil such as Vertisols, Degraded Bar Land, and No Degraded Bar Land.…”
Section: Discussionmentioning
confidence: 63%
“…These crops are rice, sorghum, small millet, millet, cotton, bean, cowpea, cassava, bambara groundnut, yam, and pimento. In southern Benin, except maize, Adjanohoun et al [26] had identified cotton, groundnut, sweet potato, cowpea, and cassava. These cultures were mostly found in northern and central Benin.…”
Section: Discussionmentioning
confidence: 99%